2023
DOI: 10.3390/met13101724
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Weldability of Additively Manufactured Aluminium Parts by Fusion and Solid-State Welding Processes

Rafael Nunes,
Koen Faes,
Wim De Waele
et al.

Abstract: Additive manufacturing (AM) processes are playing a significant role in several industrial sectors such as construction and machine building industries, involving a wide variety of metallic materials. Among these, the AM of aluminium alloys has developed significantly over the last decade, mainly through Powder Bed Fusion (PBF) and Directed Energy Deposition (DED) processes. Despite the many advantages of AM technology, some large or complex products cannot be produced entirely without the use of conventional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…Nunes et al [ 21 ] conducted a comprehensive review focusing on the weldability of Al alloys processed by additive PBF‐L. Their detailed study revealed that among the various fusion welding processes, EBW was found to be the most suitable process for welding Al alloys, providing consistently higher tensile strength values.…”
Section: Introductionmentioning
confidence: 99%
“…Nunes et al [ 21 ] conducted a comprehensive review focusing on the weldability of Al alloys processed by additive PBF‐L. Their detailed study revealed that among the various fusion welding processes, EBW was found to be the most suitable process for welding Al alloys, providing consistently higher tensile strength values.…”
Section: Introductionmentioning
confidence: 99%